(untitled) (MAUSAM, 1978)
Typical of the monsoonal rainfall conditions over Sri Lanka are the remarkable inter-annual and seasonal deficits of water, varying considerably in temporal and spatial aspects. Therefore, both the phenomena of aridity and drought are of great significance from the point of the general monsoon climate of Sri Lanka. This paper investigates the annual and monthly aridity by using the ’aridity index’ of De Martonne Lauer (1926/1952) showing the increasing extent of aridity from the S. W. quarter to the N.W./N as well as S.E. of Sri Lanka. On the other hand, drought has been studied by the ’drought index’ of Gibbs and Maher (1967) underlining a considerable interannual rainfall variability, being expressed by the incidence of heavily drought-stricken years as well as by the occurrence of completety drought-free years. It is pointed out that drought can be called a typical, however irregular and spatially limited phenomenon in the climate of Sri Lanka. All observations are based on 30-year rainfall data (1931-1960) of monthly and annual figures.